Logic Structure of Means Used for Higher Dynamic Stability of Power Transmission Systems - G. E. Pospelov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains a proposal for classification of means used for higher dynamic stability of power transmission systems on the basis of a differential equation of generator rotor motion which makes possible to estimate efficiency of these means.